2020
DOI: 10.1038/s41598-020-72507-4
|View full text |Cite
|
Sign up to set email alerts
|

Native bacteria isolated from roots and rhizosphere of Solanum lycopersicum L. increase tomato seedling growth under a reduced fertilization regime

Abstract: In semiarid regions is important to use native strains best adapted to these environments to optimize plant-PGPR interaction. We aimed to isolate and characterize PGPR from roots and rhizosphere of a tomato crop, as well as studying the effect of its inoculation on tomato seedlings growth. We selected four strains considering their effectiveness of fixing nitrogen, solubilizing phosphate, producing siderophores and indole acetic acid. They belong to the genera Enterobacter, Pseudomonas, Cellulosimicrobium, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…As a result, the amount of OH − released was minimal, resulting in a pH drop in the soil. These findings are consistent with the literature associated with effects of bioinoculants on plants under a reduced fertilization regime [ 44 , 48 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, the amount of OH − released was minimal, resulting in a pH drop in the soil. These findings are consistent with the literature associated with effects of bioinoculants on plants under a reduced fertilization regime [ 44 , 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…application resulted in a consistent increase in SAP along with an increase in soil bacterial viable cells. Pérez-Rodriguez et al [ 44 ] supports this finding, as they confirmed the presence of a pqq -encoding gene in the genomic DNA of Enterobacter sp., which is responsible for P solubilization as a cofactor in glucose extracellular oxidation to gluconic acid via glucose-dehydrogenase-mediated processes. This data concurs with our prior observation that strain 40a generated a huge amount of gluconic acid during P and K solubilization [ 23 ].…”
Section: Discussionmentioning
confidence: 71%
“…The NaCl tolerance was assessed in four bacterial strains ( Enterobacter 64S1, Pseudomonas 42P4, Ochrobactrum 53F, and Cellulosimicrobium 60I1) previously isolated from roots and the rhizosphere of tomato (Pérez‐Rodriguez et al, 2020). These bacteria are able to solubilize different sources of inorganic phosphate to fix N 2 , to produce siderophores and indole acetic acid (Pérez‐Rodriguez et al, 2020). Salt tolerance was determined in solid Luria‐Broth medium (LB, Sigma Chem.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we isolated and identified four PGPR strains that increase tomato seedling growth (Pérez-Rodriguez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation